-10x+2x+(-4+9)=-8x+5

Simple and best practice solution for -10x+2x+(-4+9)=-8x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10x+2x+(-4+9)=-8x+5 equation:



-10x+2x+(-4+9)=-8x+5
We move all terms to the left:
-10x+2x+(-4+9)-(-8x+5)=0
We add all the numbers together, and all the variables
-10x+2x-(-8x+5)+5=0
We add all the numbers together, and all the variables
-8x-(-8x+5)+5=0
We get rid of parentheses
-8x+8x-5+5=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| a-20=32 | | x=2/3x-7 | | -7(4x+6)=-(5x+1) | | d+36=58 | | 2x+12+19=x+16 | | 25-a=2 | | 2.5x+30=150 | | t-23=24 | | w-8=15 | | 2y-4=13 | | 4^1-2x=0.0625 | | 22x=66x= | | 100=t+25 | | 114=3(y+1 | | 2π(9)+2π(3)(8)=s | | 2(3.14)(9)+2(3.14)(3)(7)=s | | 5+20m−2m=-13 | | t+15=99 | | 56+68+x+66=180 | | 3x​ +1=11 | | x^2=9*15 | | 3.6/x=10.8/12 | | 15q=60,q= | | ​3​​x​​-11=-5 | | 12x−1=11 | | 5^7•5n=5^10 | | 9x-7=-9+15 | | -x2-5x+1=22 | | 0.5=0.2+x-0.2x | | 6b+4b+40=180 | | 25^3r=5^3 | | 6b+4b=40 |

Equations solver categories